2012
DOI: 10.1186/1746-1596-7-10
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma involving the gallbladder: a retrospective review of 23 cases - pitfalls in diagnosis of gallbladder carcinoma

Abstract: BackgroundCarcinoma of the gallbladder (GBC) clinically mimics benign gallbladder diseases and often escapes detection until advanced stage. Despite the frequency of cholecystectomy, diagnosis of GBC remains problematic in many situations. We sought to identify pathologic features that contribute to the difficulty in recognition of GBC.MethodsWe identified 23 patients (ranged from 45 to 86 years, male to female ratio 1:4.5) with carcinoma involving the gallbladder referred to an academic medical center over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…Underdiagnosis and overdiagnosis -both are not uncommon in gall bladder cancer (Giang et al, 2012). Marked necrosis, extensive fibrosis with few tumor cells, limited invasion with dysplastic glands-are some difficult situations which we encountered especially in unsuspected cases.…”
Section: Discussionmentioning
confidence: 99%
“…Underdiagnosis and overdiagnosis -both are not uncommon in gall bladder cancer (Giang et al, 2012). Marked necrosis, extensive fibrosis with few tumor cells, limited invasion with dysplastic glands-are some difficult situations which we encountered especially in unsuspected cases.…”
Section: Discussionmentioning
confidence: 99%
“…The gallbladder is anatomically characterized by its location in relation to the surrounding organs, the absence of a musclaris mucosae, presence of Rokitansk-Aschoff sinuses [1,2], presence of a very thin muscularis propria composed of a network of smooth muscle cells, and abundance of blood and lymph vessels in the subserosa. Therefore, once gallbladder cancer crosses the mucosal layer, it easily penetrates the muscular coat to invade the subserosa and spread into the abundant blood and lymph vessels, leading to increased invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Dysplasia extending to Rokitansky-Aschoff sinuses (RAS) can mimic adenocarcinoma [22] . Giang et al [23] reported two cases of surface dysplasia which on further evaluation demonstrated numerous areas in which dysplasia was Annals of Pathology and Laboratory Medicine, Vol. 5, Issue 1, January, 2018 seen extending into RAS, mimicking transmural invasion of carcinoma.…”
Section: Histopathological Mimic Of Gbcmentioning
confidence: 99%
“…Giang et al [23] reported adenomyosis can be confused with adenocarcinoma. It can be differentiated from adenocarcinoma by noting cytology of glands which are usually benign in cases of adenomyomatosis.…”
Section: Histopathological Mimic Of Gbcmentioning
confidence: 99%